Metabolomics revealed pharmacodynamic effects of aspirin and indobufen in patients after percutaneous transluminal angioplasty surgery - Sun, Shaobo; Xun, Kang; Li, Damei; Bao, Renjie (Frontiers in Cardiovascular Medicine, 2024)
Aspirin and indobufen are commonly used therapeutic drugs for the prevention of vascular restenosis (VR) after percutaneous transluminal angioplasty surgery. They both exhibited antiplatelet effects but molecular mechanisms underlying metabolic changes induced by them remain unclear. In this study, we collected plasma samples from patients on aspirin medication (n=5), patients on indobufen medication, patients with no medication after PTA, and healthy controls (CKs) (n=5). Our investigation aimed to reveal the metabolic processes in patients during vascular restenosis and its amelioration through drug therapy using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Our data showed significant alterations in amino acid and choline metabolism in patients without medication after PTA. Aspirin and indobufen were able to regulate these metabolic pathways to alleviate VR symptoms. We identified several characteristic amino acids, including pro-leu, L-citrulline, his-glu, and L-glutamate, as important biomarkers for VR assessment in patients without medication after PTA. A total of 17 and 4 metabolites involved in arginine and phenylalanine metabolism were specifically induced by aspirin and indobufen, respectively. Their expression levels were significantly regulated by aspirin or indobufen, nearly reaching normal levels. Taken together, our identification of metabolites involved in metabolic changes affected by aspirin and indobufen medication enhances the understanding of VR pathology after PTA. This may help identify early diagnostic biomarkers and therapeutic targets.